If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 6 + 6x + -2 + 2 + -2x = 6x + 12 + x + 15 Reorder the terms: 6 + -2 + 2 + 6x + 6x + -2x = 6x + 12 + x + 15 Combine like terms: 6 + -2 = 4 4 + 2 + 6x + 6x + -2x = 6x + 12 + x + 15 Combine like terms: 4 + 2 = 6 6 + 6x + 6x + -2x = 6x + 12 + x + 15 Combine like terms: 6x + 6x = 12x 6 + 12x + -2x = 6x + 12 + x + 15 Combine like terms: 12x + -2x = 10x 6 + 10x = 6x + 12 + x + 15 Reorder the terms: 6 + 10x = 12 + 15 + 6x + x Combine like terms: 12 + 15 = 27 6 + 10x = 27 + 6x + x Combine like terms: 6x + x = 7x 6 + 10x = 27 + 7x Solving 6 + 10x = 27 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 6 + 10x + -7x = 27 + 7x + -7x Combine like terms: 10x + -7x = 3x 6 + 3x = 27 + 7x + -7x Combine like terms: 7x + -7x = 0 6 + 3x = 27 + 0 6 + 3x = 27 Add '-6' to each side of the equation. 6 + -6 + 3x = 27 + -6 Combine like terms: 6 + -6 = 0 0 + 3x = 27 + -6 3x = 27 + -6 Combine like terms: 27 + -6 = 21 3x = 21 Divide each side by '3'. x = 7 Simplifying x = 7
| (V+7)(v+1)=0 | | .5(5x-10)=-35 | | 18m-31=51 | | u+327-15= -11 | | 7.2x-5.9(x-1)=7.9 | | -14/-6=-84 | | (2r-7)(2r+3)=0 | | 20y=5x+8 | | 20=5x+8 | | (8m+3)(2m+9)=0 | | 8x-7+3x=37 | | 72-p=75 | | .09x+.07y=1760 | | m-74=54 | | 4(1-8n)-5n=-292 | | 6(r+84)=-18 | | 6d-12/2=2d-13/2 | | 2c+9=29 | | 55=5+5a | | 9(x+8)=5[x-(9-x)] | | 8v^2+10v=9 | | 6x=-3(-2x-1)-3 | | s-1/3=2/3 | | -3u+15=6u+24 | | -4(k+94)=-20 | | 8x+12x=60 | | -12x-91=6x+35 | | F(39)=15-x/13 | | 15-X+8=53 | | S-5=2s | | 1-z=4 | | -9x-8=-10x+16 |